2014
DOI: 10.1016/j.aju.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and reproducibility of ultrasonography for measuring the residual urine volume in men with lower urinary tract symptoms

Abstract: ObjectiveTo assess the reliability and reproducibility of abdominal ultrasonography (US) for measuring the postvoid residual urine volume (PVR), and to compare measurements by a radiologist and urologist, in men with lower urinary tract symptoms (LUTS), as a significant PVR is common in patients with LUTS and an assessment of the PVR could protect patients from unnecessary catheterisation.Patients and methodsThis was a prospective comparative study of 45 men aged ⩾45 years with LUTS attending a urological outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In most of the studies, ultrasonographic PVR measurement with an automated real-time calculation is found to be as affective as catheterization [7][8][9][10]. However other studies found this modality to be limited and less accurate than catheterization [6,11]. In the studies that are against the use of ultrasonographic PVR measurement, we see that conventional ultrasonograhy was used to measure PVR.…”
Section: Discussionmentioning
confidence: 95%
“…In most of the studies, ultrasonographic PVR measurement with an automated real-time calculation is found to be as affective as catheterization [7][8][9][10]. However other studies found this modality to be limited and less accurate than catheterization [6,11]. In the studies that are against the use of ultrasonographic PVR measurement, we see that conventional ultrasonograhy was used to measure PVR.…”
Section: Discussionmentioning
confidence: 95%
“…Although UC is reliable method, it is invasive and cause distress in children. UC has also cause urethral trauma and urinary tract infection (7). Rosseland et all (8) found that the bladder emptying with catheter was in complete in 30 % of patients and cause wrong measurement of PVR.…”
Section: Discussionmentioning
confidence: 99%
“…[5] PVR can be measured by transabdominal ultrasound, which is a simple, accurate, and noninvasive method. [6] However, a feeling of incomplete emptying does not always strongly correlate with measured PVR volume. [7] Urologists occasionally encounter men with LUTS complaining of a feeling of incomplete emptying despite no or little PVR.…”
Section: Introductionmentioning
confidence: 99%